Certain Coefficient Estimate Problems for Three-Leaf-Type Starlike Functions - Lei Shi; Muhammad Ghaffar Khan; Bakhtiar Ahmad; Wali Khan Mashwani; Praveen Agarwal; Shaher Momani (Fractal and Fractional, 2021)
In our present investigation, some coefficient functionals for a subclass relating to starlike functions connected with three-leaf mappings were considered. Sharp coefficient estimates for the first four initial coefficients of the functions of this class are addressed. Furthermore, we obtain the Fekete–Szegö inequality, sharp upper bounds for second and third Hankel determinants, bounds for logarithmic coefficients, and third-order Hankel determinants for two-fold and three-fold symmetric functions.